Annual Plan 1986-87 Government of Mizoram - Planning Commission (Planning Commission, 1986)
The Union Territory of Mizoram lies in the North Eastern Corner of India between Tripura and Bangladesh in the W est Burma in the. East and. South.. In the North it has a boundary with Manipur and. Cachar District of Assam State. Mizoram has an area of 21,081 Sq.Km with a population of 4,93,757 (according 1981 Census).Most of the areas are covered, by sharp ranges interspered with deep gorged terrains. the hills range mostly from North to South. The average elevation is 914 metres above see level.
Planning Department Government of Mizoram